Earnings Growth and Acquisition Returns: Do Investors Gamble in the Takeover Market? - Liu, Tingting; Tu, Danni (Journal of Financial and Quantitative Analysis, 2023)
Abstract We document a strong positive initial market reaction to merger announcements from bidders with either large earnings growth or significant earnings decline, relative to those with neutral earnings change, reflecting a U-shaped pattern between bidders’ earnings growth and announcement returns. However, the higher initial returns for bidders with earnings decline subsequently reverse, whereas the higher returns for bidders with high growth do not. We further show that the return patterns are driven by a tendency for retail investors to gamble that merger and acquisition deals initiated by poorly performing bidders will generate high synergies.